ISLAM DAN CABARAN SEKULARISME DI TANAH MELAYU: ANALISA KITAB JAWI TERPILIH - Ahmad Farid Abd Jalal; Rahimin Affandi Abdul Rahim; Ahnaf Wafi Alias (FISIP UIN SGD Bandung, 2018)
This paper investigates how the response of Malay Islamic intellectualism to the challenges of globalizing secularism. With the library approach, it can be emphasized that researchers have proven the eternal nature of classical Malay books in the face of the challenges of modernization that arise in society. This can be seen from the discussion about the issue of epistemology, world-view and changes in society in these books. In the estimation of the academic world, all of this evidence shows the ability of classical Malay books to solve the problems of the Islamic ummah, even though they were allegedly perceived as an old inheritance.